2021
DOI: 10.1128/msphere.00250-21
|View full text |Cite
|
Sign up to set email alerts
|

Term Human Placental Trophoblasts Express SARS-CoV-2 Entry Factors ACE2, TMPRSS2, and Furin

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has had a massive impact on human lives worldwide. While the airborne SARS-CoV-2 primarily affects the lungs, viremia is not uncommon. As placental trophoblasts are directly bathed in maternal blood, they are vulnerable to SARS-CoV-2. Intriguingly, the human fetus is largely spared from SARS-CoV-2 infection. We tested whether the human placenta expresses the main SARS-CoV-2 entry factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 90 publications
0
39
0
1
Order By: Relevance
“…Recent study demonstrated the expression of the main SARS-CoV-2 cellular entry factors in villous trophoblast in term placentas, explaining why this cellular layer gets attacked by the virus [ 24 ]. The individual variability of these expression levels may be responsible for the different susceptibility to placental infection among women.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study demonstrated the expression of the main SARS-CoV-2 cellular entry factors in villous trophoblast in term placentas, explaining why this cellular layer gets attacked by the virus [ 24 ]. The individual variability of these expression levels may be responsible for the different susceptibility to placental infection among women.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is an active peptide of the renin–angiotensin system (RAS) which has been given considerable attention as a potential target for anti-viral therapeutics [ 6 ], since it is the main cell entry receptor of SARS-CoV-2 [ 7 ]. Other SARS-CoV-2 cell entry proteins have been described [ 8 ]. However, ACE2 is predominantly expressed in the syncytiotrophoblast layer (which directly faces the maternal blood), compared to other SARS-CoV-2 cell entry proteins [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based upon the observations made in recent articles describing the pathology findings from infected placentas, it can be confidently stated that the syncytiotrophoblast is the most frequent cell type composing the maternal-fetal interface to be infected with SARS-CoV-2 [28]. The syncytiotrophoblast expresses the major cell surface receptor for SARS-CoV-2, angiotensin-converting enzyme 2 (ACE2), throughout gestation [43,44]. Because of its strategic location on the surface of the syncytiotrophoblast, this receptor is exposed directly to maternal blood that circulates through the intervillous space, and which may contain SARS-CoV-2 in infected pregnant women with viremia.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its strategic location on the surface of the syncytiotrophoblast, this receptor is exposed directly to maternal blood that circulates through the intervillous space, and which may contain SARS-CoV-2 in infected pregnant women with viremia. In addition to ACE2, the syncytiotrophoblast also expresses the SARS-CoV-2 entry factors transmembrane protease serine 2 (TMPRSS2), and furin [44,45]. Recent evidence has suggested that in contrast to 1st and 2nd trimester placentas, there is low expression of the ACE2 viral receptor on placental trophoblast cells during the later stages of pregnancy [46,47], potentially accounting for the relatively low rate of transplacental transmission that occurs with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%